MENINGKATKAN KETERAMPILAN MEMBUAT SANJAI TAWAR MENTAH MELALUI BANTUAN TUTOR SEBAYA PADA ANAK TUNAGRAHITA RINGAN - Azimar - - (Universitas Negeri Padang, 2014)
This research is motivated by problems in the field that appears Tunagrahita Lightweight four children who are learning the skills to make fresh Sanjai menta . Of the four students who take only two students who otherwise completed using a 10 -making process . The two students appointed as peer researchers to help two students again that the four students who studied skilled in making Sanjai fresh raw. This study uses action research ( Classroom Action Research ) in collaboration with colleagues . Data were collected through observation techniques , and tests , then analyzed qualitatively and quantitatively . Subjects were Tunagrahita Lightweight Kids in Class V SLB sparkle Tarusan the initials AR , FD , DW , and GN . This research was conducted in two cycles , the first cycle with a 5 second cycle with meetings and 4 meetings . The results of the assessment ( initial test ) capability AR (50 %) , FD ( 50 % ) , DW ( 20 % ) and GN ( 30 % ) . AR cycle I got the results ( 100 % ) , FD ( 100 % ) , DW ( 50 % ) and GN gets the value ( 50 % ) . In the second cycle AM gets the value ( 100 % ) , FD gets the value ( 100 % ) , MY scored (100 %) and YS get value ( 100 % ) This shows the increase and success after allowing for repair and the role of peers in helping Sanjai raw fresh made ​​. It can be concluded that the method can improve the skills of peer tutors make fresh raw Sanjai for mild mental retardation children , it is recommended to teachers in order to implement a peer tutoring methods to improve the skills of the child .